La influencia del consumo de internet en la comunicación entre adolescentes de la Unidad Educativa Isla de Bejucal - Carvajal Verdezoto, Elvis Emilio (2018)
In this research we seek to understand the influence of internet consumption on communication relationships among adolescent students of the "Isla de Bejucal" Educational Unit, once the problem was identified, the investigation was carried out, as well as being theoretically based to verify the hypothesis that Internet consumption influences communication relationships between adolescents and parents in the "Isla de Bejucal" Educational Unit, which may be transforming adolescents' values, behaviors and life expectancies. get to cause tensions with the ideas that parents have with respect to their children, based on the differentiated consumption of the Internet. Once the investigative process was completed, it could be shown that the internet has made students change their behavior and expectations about communication relationships with other adolescents and their parents, and a proposal was made based on a communicational campaign. directed to parents, teachers and children to educate them about the use of the internet.